AMYLASE ACTIVITY IN PANCREAS TISSUES AND BLOOD SERUM AT BURN DISEASE - Харченко, С.В. (World of Medicine and Biology, 2016)
In an experimental model of burn disease studies damages internal organs and their correction [4, 6, 7]. But not well understood at burn disease changes in the pancreas that creates enzymes having proteolytic, amylolytic and lipolytic action. The pancreas is an organ in which inactive proenzymes are formed and released into the intestine. In the cavity of the duodenum proenzymes are activated and participate in the digestion of proteins, fats and carbohydrates. If the effect of the factors causing damage to cells of the pancreas, it is legitimate to assume that enzymes of destroyed pancreas cells will flow in the blood, but will not receive the intestine. In addition, the effects of various unfavorable can change structure of the enzyme protein, which will lead to increase or decrease their activity. The enzyme α-amylase of a pancreas breaks down carbohydrates homopolysaccharides starch and glycogen involving water. These homopolysaccharides formed from the remnants of glucose. Polysaccharide molecules have the following fractions: amylose and amylopectin. Amylose is a linear faction, formed from the remnants of glucose connected α-1,4-glycosidic bonds. The enzyme α-amylase cleaves α-1,4-glycosidic bonds in amylose molecules. The end product of the reaction is disaccharide maltose, which is formed of 2 glucose residues. Previous studies have found that α-amylase activity in pancreatic tissue of rats with acute stress, increased 1.5 times compared with control [1]. The activity of α-amylase in serum of rats with acute stress, increased 1.5 times compared with control [1]. The activity of α-amylase in duodenal intestinal fluid in rats with acute stress is reduced by 1.5 times, compared with control [1]. Revealed morphological changes – destruction of pancreatic tissue in acute stress [1]. Perhaps the enzyme α-amylase arising from the damaged pancreas in blood and does not enter to the intestines. The aim of study was to investigate changes in amylase activity in pancreatic tissue and serum of rats with experimental burn disease. Experiments were performed on 15 white male rats weighing 180 – 250 g of burn disease. The method of Довганского was used by dipping the rear extremity of experimental animals in hot water (t = +70 – 75º C) under light ether anesthesia for 7 seconds. Under these conditions produced a burn. Animal euthanasia was performed on the first and seventh day under ether anesthesia. In pancreatic tissue homogenate and serum amylase activity was determined by weight starch, which is subject to hydrolytic cleavage. Amylase activity in pancreatic tissue of control rats written as 100%. When it is burn disease, on the first day after the burn amylase activity in pancreatic tissue is increased by 1.3 times compared to the control (p < 0.05). In the burn shock stage (the 1-st day) amylase activity increased in homogenate pancreatic tissue by 26% compared with the control. On the seventh day after the burn amylase in the tissues of the pancreas is reduced by 1.2 times compared to the first day (p